An Examination of 4 Questions Assessing Self-reported Concussions Among High School Students Participating in Team Sports. Issue 2 (March 2020) - DePadilla, Lara; Miller, Gabrielle F.; Jones, Sherry Everett
Abstract : Objective: Current prevalence estimates of youth sports-related concussions are inconsistent because of variation in methodology and potentially unreported concussions. Methods: In 2013, Connecticut, Ohio, and Utah each added different questions that assessed self-reported concussions to the Youth Risk Behavior Survey. Two questions referenced recognition of a concussion by the student, 1 referenced identification by a doctor, and 1 referenced suspicion by a coach. Chi-square analyses were used to identify whether there was an association between demographic characteristics and the concussion questions among high school students who played on at least 1 sports team. Results: The percentage of students who reported concussions ranged from 17.6% to 20.1%. Conclusions: These estimates are higher than rates of concussions diagnosed in emergency departments or reported by athletic trainers but were similar across the 4 questions. The field would benefit from a better understanding of the impact of question wording and format on estimates of concussion prevalence.